Phát biểu khai mạc Kỳ họp bất thường lần thứ nhất, Quốc hội khóa XV của Chủ tịch Quốc hội Vương Đình Huệ - Vương Đình Huệ (2022)
Toàn văn Phát biểu khai mạc Kỳ họp bất thường lần thứ nhất, Quốc hội khóa XV của Chủ tịch Quốc hội Vương Đình Huệ